Leventis, Georgios - (:unkn) unknown (My University, 2026)
I was born in Athens in 1989. I studied Cultural Informatics & Communication at University of Aegean (Mytilene, Greece), where I continued my studies with an MSc in the abovementioned scientific field. Moreover, in my thesis and in my master thesis, I dealt with the Artificial Neural Networks and their training using machine learning algorithms. During my academic years, I have been member of University’s “Intelligent Multimedia & Virtual Reality” research laboratory, where alongside with my professors we published and presented our research paper entitled “A Hierarchical Fuzzy Clustering Framework for Training RBF Networks” in the proceedings of IASTED International Conference. In the past, I have worked as a Service Desk Analyst in Cosmote Mobile Telecommunications (Athens, Greece). Currently, my main interest lies in using machine learning in processing 3D/4D cultural assets.
Keywords: engineering